Belhar as mirror and window on social cohesion and justice - Fortein, Eugene Andre (Stellenbosch Theological Journal, 2023)
This study argues that the Reformed Churches in South Africa failed to constructively contribute to social cohesion and justice since the drafting of the Belhar Confession in 1982 due to its failure to embody the demands of unity, reconciliation and justice. Firstly, the study briefly discusses the historical setting of the Belhar Confession and how it remains a bridge too far to embody for the Church in South Africa since its drafting in 1982. Furthermore, the study indicates how the Church’s failure to embody the Belhar Confession leaves a vacuum in the discourses on racial tensions, the land issue and the new apartheid. Finally, the study engages how the Church can be an agent of transformation and hope.